PHENOMENOLOGICAL STUDY: SOCIAL MEDIA AS A SHAPING OF ADOLESCENT IDENTITY - Maswita; Muhammad Fadli (CV. Mitkom Indotama, 2025)
The internet and teenagers are two interrelated things in the life of modern society. Data from the Ministry of Communication and Information Technology shows that the use of the internet among teenagers is mostly used to access social media. This phenomenon is interesting to study because social media is an important space for teenagers to build and express their identity. This study aims to analyze the role of social media in the formation of adolescent identity as well as how adolescents express personal problems in the digital space. This study uses a qualitative approach with a phenomenological method. The theoretical frameworks used include Identity Theory, Symbolic Interaction Theory, and Media Ecology Theory. The data was obtained through in-depth interviews with adolescents who actively use social media. The results of the study show that adolescents display diverse identities on social media and tend to express personal problems indirectly or implicitly. Social media plays an important role in the construction of adolescent identity in the digital era.